Classroom questions and their role in educational achievement Arabic language textbook questions for secondary education as a model : A critical view - Touahri, Salah (Journal of Human Sciences, 2021)
Since the beginning of the modern era, educational scientists have been keen to know the reasons for improving the level of learners and diagnosing their knowledge and abilities, as their focus was great on knowing the most effective methods of teaching and its best methods and elements of the educational process and its multiple components, and perhaps the class questions are among the most prominent methods and mechanisms that educators have been interested in researching. Being an important means of communication between the teacher and the learner, as it works to create conditions for learning; As it opens bridges of communication and ways of dialogue between learners, reveals their various abilities, and sends a spirit of scientific competition among them, so as to allow them the opportunity to express opinion.